ACADEMIC FRAUD BEHAVIOR OF ACCOUNTING STUDENTS: FRAUD DIAMOND DIMENSIONS - Ana Mardiana; Anthony Holly (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – The purpose of this study was to investigate the behavior of academic fraud on accounting students at Atma Jaya Makassar University using the concept of diamond fraud, namely pressure, opportunity, rationalization, and ability. This type of research is quantitative research. Design/methodology/approach – Questionnaires were distributed to 120 respondents and processed using the SPSS assistance program. Findings – The results of this study indicate that pressure has an insignificant effect, opportunity has a significant positive effect on academic violation behavior, rationalization has a significant negative effect and opportunity has a significant negative effect. Originality – The population in this study were accounting students at Atma Jaya Makassar University using the purposive sampling method with the condition that students were or were taking Auditing I and Auditing II courses namely the 2017 and 2018 class students.